Wheat Variety Test Results for South Central Kansas - 2022 - Jeffrey Seiler; Randy Hein; Ryan Flaming; Jennifer Carr; Romulo Lollato; Bruno C. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2023)
South central Kansas is the highest producing wheat region in Kansas. This report summarizes the results of winter wheat variety tests for 2021-2022 in six locations.
Keywords: grain yield; test weight; variety selection; production systems